The Normality of EU Sport Policy Studies: Disciplinary Locus in Political Science, Sport Science or Elsewhere? - Jacob Kornbeck (Karolinum Press, 2014)
The Normality of EU Sport Policy Studies: Disciplinary Locus in Political Science, Sport Science or Elsewhere? Mainstream European integration research has shown that research on the EU tends to follow the conjunctures of European integration itself. This realisation has led to some debate on which branch of political science - international relations or government - or indeed other academic disciplines is/are the most appropriate locus for such research. The paper takes these debates one step further by looking at the occurrence of 'EU & sport' studies within the wider field of EU studies. The main material used comes from the ECLAS database. Findings lead to a discussion of whether 'EU & sport' studies should rather be for EU specialists or for sport specialists and a plea for disciplinary normalisation whereby sport science would need to get more directly involved (without necessarily overwriting political science). Some ideas are added regarding the need for a mapping of Central & Eastern European scholarship. Normalita politických studií EU v oblasti sportu: místo v oborech politologie, sportovních vědách či jinde? Hlavní integrační proudy v evropském výzkumu dokumentují, že výzkum v EU má tendenci zkoumat evropskou integraci jako takovou. Toto poznání vedlo k diskusi, v kterém oboru politologie - mezinárodní vztahy či vláda - nebo i v jiných akademických disciplínách je nejvhodnější místo pro takový výzkum. Stať se pokouší posunout tyto diskuse o krok dále tím, že studie o "EU a sportu" se posuzují v širším záběru EU studií. Hlavní informační zdroje pocházejí z databáze ECLAS. Naše zjištění vedou k diskusi o problematice "EU a sportu" v tom smyslu, zda by tyto studie měly být spíše určeny odborníkům EU, nebo sportovním specialistům. Důležitá je otázka disciplinární začlenění této problematiky, s širším zapojením sportovních věd (aniž by se nutně přepisovaly politické vědy). Některé přidané myšlenky se týkají potřeb stipendií pro země Střední a Východní Evropy.